Comparison of Exosome- and Hybrosome-Based Therapies in Regenerative Medicine and Cell Aging: A Narrative Review - Cohen, Steven R.; Wesson, Jordan; Canikyan, Serli; Tiryaki, Tunc; Kul, Yaren; Duyan, Ceren (OXFORD UNIV PRESS INC, 2026)
Exosomes have emerged as promising agents in regenerative medicine because of their ability to mediate intercellular communication, modulate inflammation, and promote tissue repair. However, their clinical application remains limited by issues of stability, bioavailability, and therapeutic consistency. Hybrosomes, engineered hybrid vesicles that combine exosomal membranes with liposomal structures, have been developed to enhance delivery, protect bioactive cargo, and prolong regenerative activity. The authors of this review aim to discuss the therapeutic efficacy of exosomes and hybrosomes in the context of skin regeneration and aesthetic procedures and evaluate their respective advantages and limitations. They aim to explore how bioengineered delivery systems may overcome current barriers to clinical translation. Studies were included if they evaluated exosome- or hybrosome-based interventions in wound healing or skin aging through in vitro, in vivo, or clinical models. Data regarding cellular proliferation, migration, angiogenesis, and inflammatory modulation were extracted and synthesized. The improved stability and delivery of hybrosomes enables sustained regenerative effects. The integration of liposomal architecture in hybrosomes may improve vesicle stability, extend bioactivity, and optimize delivery, potentially offering sustained regenerative benefits. However, future studies should include long-term clinical evaluations and standardized production protocols to establish hybrosome therapies as reliable and scalable interventions in regenerative and aesthetic medicine.Level of Evidence: 3 (Therapeutic)
Keywords: EXTRACELLULAR VESICLES; PLURIPOTENT; Surgery